Effect of apple pomace silage on blood parameters in Suffolk ewe: Apple pomace silage in ewes - Islam, S; Islam, MN; Matsuzaki, M (Bangladesh Journal of Animal Science, 2018)
The experiment was carried out to assess the effects of feeding apple pomace silage (APS) on blood parameters in Suffolk ewes. Three ewes were used in 3×3 Latin square design over three periods with three dietary treatments as hay diet, low ethanol APS (L-APS, ethanol 48.7 g kg-1 DM) diet and high ethanol APS (H-APS, ethanol 87.2 g kg-1 DM) diet. Alfalfa hay cube and APS provided half of 110% TDN requirement for APS diets. The area upper or under the curve (AUC) of plasma ethanol was greater (P<0.01) in APS diets than that of hay diet and H-APS diet had grater (P<0.01) AUC than that of L-APS. The AUC of plasma β-hydroxybutyrate in both APS diets were greater (P<0.01) than that of hay diet. Plasma ethanol AUC was positively correlated (P<0.05) with the AUCs of plasma lactate, triglyceride and glutamate oxaloacetate transaminase (GOT), and negatively correlated (P<0.05) with the AUC of plasma urea nitrogen. Plasma lactate AUC was positively correlated (P<0.05, P<0.01, and P<0.05, respectively) with the AUC of free cholesterol, triglyceride and GOT, and negatively correlated (P<0.01) with that of plasma urea nitrogen. The AUC of plasma β-hydroxybutyrate was negatively correlated (P<0.01) with that of glucose. Finally, blood parameters examination revealed that feeding of APS lead to increase plasma ethanol, lactate, β-hydroxybutyrate and lipid components and tended to decrease glucose levels. Bang. J. Anim. Sci. 2018. 47 (2): 51-60